Investigation of anger levels in adolescent individuals in terms of educational game variable - Mehibe Akandere (Türk Spor ve Egzersiz Dergisi)
This study was carried out in order to investigate anger levels of adolescent students between 15 and 16 years old.The sample of the research constituted of 52 students (experiment group) who participated in physical education course and were applied 8-week educational play program regularly at the end of the course and other 52 students (control group) who participated in physical education course but were not applied educational play program. In order to determine anger levels of students, State-Trait Anger Scale developed by Spielberger was used. In dependent groups, paired t test was applied while unpaired t test was applied in independent groups.  As a result, a significant difference was determined between pre-test and post-test values of Trait Anger, Anger Control, Anger Expression and Anger Suppression sub-dimensions of males and females participated in the research as experiment group. In control group, on the other hand, it was indicated that the scores of Anger Expression and Anger Suppression sub-dimensions of just females differed statistically and a significant difference was not found in Trait Anger and Anger Control sub-dimensions.